Cross-cultural performance management : transcending theory to a practical framework /: transcending theory to a practical framework. (2022) - Moussa, Mahmoud; Doumani, Thomas; McMurray, Adela; Muenjohn, Nuttawuth; Deng, Ling
No abstract available